Increased central auditory gain in 5xFAD Alzheimer’s disease mice as an early biomarker candidate for Alzheimer’s disease diagnosis - Na, Daxiang; Zhang, Jingyuan; Beaulac, Holly J.; Piekna-Przybylska, Dorota; Nicklas, Paige R.; Kiernan, Amy E.; White, Patricia M. (Frontiers in Neuroscience, 2023)
Alzheimer’s Disease (AD) is a neurodegenerative illness without a cure. All current therapies require an accurate diagnosis and staging of AD to ensure appropriate care. Central auditory processing disorders (CAPDs) and hearing loss have been associated with AD, and may precede the onset of Alzheimer’s dementia. Therefore, CAPD is a possible biomarker candidate for AD diagnosis. However, little is known about how CAPD and AD pathological changes are correlated. In the present study, we investigated auditory changes in AD using transgenic amyloidosis mouse models. AD mouse models were bred to a mouse strain commonly used for auditory experiments, to compensate for the recessive accelerated hearing loss on the parent background. Auditory brainstem response (ABR) recordings revealed significant hearing loss, a reduced ABR wave I amplitude, and increased central gain in 5xFAD mice. In comparison, these effects were milder or reversed in APP/PS1 mice. Longitudinal analyses revealed that in 5xFAD mice, central gain increase preceded ABR wave I amplitude reduction and hearing loss, suggesting that it may originate from lesions in the central nervous system rather than the peripheral loss. Pharmacologically facilitating cholinergic signaling with donepezil reversed the central gain in 5xFAD mice. After the central gain increased, aging 5xFAD mice developed deficits for hearing sound pips in the presence of noise, consistent with CAPD-like symptoms of AD patients. Histological analysis revealed that amyloid plaques were deposited in the auditory cortex of both mouse strains. However, in 5xFAD but not APP/PS1 mice, plaque was observed in the upper auditory brainstem, specifically the inferior colliculus (IC) and the medial geniculate body (MGB). This plaque distribution parallels histological findings from human subjects with AD and correlates in age with central gain increase. Overall, we conclude that auditory alterations in amyloidosis mouse models correlate with amyloid deposits in the auditory brainstem and may be reversed initially through enhanced cholinergic signaling. The alteration of ABR recording related to the increase in central gain prior to AD-related hearing disorders suggests that it could potentially be used as an early biomarker of AD diagnosis.